Food sovereignty at the organizational level: a framework for characterizing the diversity of economic actors - Middendorf, Matthias; Herzig, Christian (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe food sovereignty concept intends to transform agri-food systems toward justice and sustainability. While the food sovereignty movement advocates economic alternatives, the actors engaged in economic activities and striving for food sovereignty as actors of change remain overlooked. Food sovereignty scholarship and the movement gives several exemplars such as peasants, local farms and Community Supported Agriculture (CSA), as well as activities such as local food processing. However, recognition of these exemplars as ‘economic actors’ is rarely explicit, nor are their ‘economic activities’ recognized. Simultaneously, large corporations are criticized for their global market dominance, which has led to generalized negative perceptions of economic actors. This lack of differentiation, along with the absence of a clear conceptualization of Economic Actors striving for Food Sovereignty (EAFS), contributes to blind spots. Furthermore, aspects of how EAFS are structured and organized are rarely considered at the organizational level. This has led to limitations, such as in addressing organizational challenges and developing solutions to strengthen and scale EAFS.MethodsThis study aims to conceptualize the diversity of EAFS at the organizational level by identifying patterns in food sovereignty literature. Using thematic analysis within an integrative literature review, we examined 108 publications, including some gray literature.ResultsWe propose a framework with three main themes: (i) conditions that shape EAFS, including diverse motives, which affect their (ii) economic-related characteristics along the agri-food supply chain, and their (iii) organizational-related characteristics, such as forms of property and decision-making. This framework includes 12 sub-themes each encompassing a wide spectrum of differentiation and options for distinction.DiscussionIt reveals that EAFS combines alternative and conventional elements that differ in their configurations. The economic actor perspective helps to identify a broad set of EAFS and perceive their potentiality to foster new alliances and obtain mutual support. Moreover, this study underscores that food sovereignty is also a multifaceted organizational phenomenon, emphasizing the need for organizational insights to stabilize and expand EAFS. The findings can be used by researchers, practitioners, food movements, and related alternative food concepts such as food democracy, to better understand and develop such concepts and its involved actors.